ASSESSMENT OF CYTOCHROME C OXIDASE ACTIVITY IN WHITE BLOOD CELLS OF PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - MS Hakhamaneshi (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: Chronic obstructive pulmonary disease (COPD), a lung disease which is characterized by decreased expiratory flow rates, increased pulmonary resistance and hyperinflation. In vitro studies indicate that the activity of cytochrome C oxidase (COX) can be directly regulated by the presence of molecular oxygen. The aim of this study was to assess cytochrome C oxidase activity in white cells of patients with chronic obstructive pulmonary disease. METHODS: This case-control study was performed on 42 patients under clinically stable conditions and 50 healthy sedentary volunteers of similar age. Whole blood was collected and white blood cells (WBCs) separated and lysed. The homogenates were centrifuged and the supernatants were used for total protein content, COX and citrate synthase activity. Absolute specific COX activity and relative activities were determined. FINDINGS: Mitochondrial COX activity and specific activity (absolute & relative) in WBCs were significantly increased (about 3.5 time) in patients with COPD in comparison with control samples. CONCLUSION: These results indicate that the activity of COX is increased in WBCs of patients with COPD but whether this is a primary or secondary change relevant to hypoxic condition in these patients is not clear and need further study.